Personal Development and Empowerment of Adolescents at Risk by Way of Prosocial Altruistic and Anonymous Activity: A Qualitative Perspective. (January 2018) - Einat, Tomer; Michaeli, Neli
Sahi is a unique program in Israel for adolescents at risk, based on the premise that altruistic and anonymous activities help and strengthen people who carry them out. The current research examines the factors leading juveniles at risk to be involved in the program and analyzes the impact of such activities on their behavior and perception of future. The findings are as follows: (a) Altruistic and anonymous activity is perceived as self-satisfying and as initiating feelings of behavioral independency, and (b) such activity is related to the development of self-confidence, empathy, and positive perception of the future. Implications of these results and limitations of the study are discussed.